Analysis Review on Image Compression Domain - Din, Roshidi; Jabbar Qasim, Alaa; Abdullah, Shapina; Jamel Elias, Shamsul (International Journal of Engineering and Technology, 2019)
This paper describes the types of pressure used to decrease the volume of data in lower media. This study is analyzed and categorized according to the two main types of study: Lossy Compression and Lossless compression. Each type has been studied through a number of transactions that determine the efficiency of compression files. The advantages and disadvantages for each type, which emerged from previous researches will also be discussed.Â